2017
DOI: 10.12657/denbio.078.016
|View full text |Cite
|
Sign up to set email alerts
|

Stimulation of somatic embryo growth and development in Picea spp. by polyethylene glycol

Abstract: Abstract:The objective of the presented study was to compare the effect of osmotic stress, induced by various concentrations of polyethylene glycol (PEG) MW 4000, on the development, maturation, and conversion of somatic embryos of Picea abies (model species) and P. omorika (endemic species) into somatic seedlings. Embryogenic tissue (ET) of P. abies (line A and B) and P. omorika were incubated on a maturation medium with 20 µM abscisic acid (ABA), 1 µM indole-3-butyric acid (IBA) and PEG 4000 at 0, 5, and 7.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…High exogenous auxin levels in the maintenance medium interfere with the polar auxin gradient that is established during embryogenesis and prevent correct apical-basal embryo patterning [76][77][78]. Therefore, to enable further somatic embryo development in conifers, the PGRs initially added to the induction and proliferation media are replaced with mild auxin (indole-3-butyric acid (IBA)), abscisic acid (ABA), and polyethylene glycol (PEG) [74,[79][80][81]. The elimination of auxins and cytokinins is commonly used to improve the quality of somatic embryos in conifers [82].…”
Section: Somatic Embryo Productionmentioning
confidence: 99%
See 1 more Smart Citation
“…High exogenous auxin levels in the maintenance medium interfere with the polar auxin gradient that is established during embryogenesis and prevent correct apical-basal embryo patterning [76][77][78]. Therefore, to enable further somatic embryo development in conifers, the PGRs initially added to the induction and proliferation media are replaced with mild auxin (indole-3-butyric acid (IBA)), abscisic acid (ABA), and polyethylene glycol (PEG) [74,[79][80][81]. The elimination of auxins and cytokinins is commonly used to improve the quality of somatic embryos in conifers [82].…”
Section: Somatic Embryo Productionmentioning
confidence: 99%
“…In turn, Hu et al [85] demonstrated the possibility of obtaining mature somatic embryos of Cunninghamia lanceolata after using a low NAA concentration (1.08 µM) that was eight-times lower than that of the cytokinins used. Our previous studies revealed the possibility of generating mature somatic embryos of P. abies and P. omorika after the maintenance of ETs on a medium supplemented with picloram (9 µM) and BA (4.5 µM) [80]. Comparing the effects of 2,4-D, NAA and picloram used at the proliferation stage on the maturation stage in this study, we did not observe a statistically significant impact on the number of produced SESs or embryos at the cotyledonary stage in either spruce species.…”
Section: Somatic Embryo Productionmentioning
confidence: 99%
“…It was also proven that high-molecular-weight compounds such as polyethylene glycol (PEG) 4000 had a positive effect on somatic embryo quality and increased the number of mature spruce embryos [80,82,83]. However, their impact on post-maturation development is still unclear, and further investigations are needed [80,84]. An alternative to osmotic stress treatment during the maturation stage may be reduced glutathione (GSH) application to the medium [85] or low-temperature treatment [86,87].…”
Section: Maturation Of Somatic Embryosmentioning
confidence: 99%